PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, REWARD AND PUNISHMENT TERHADAP ETOS KERJA KARYAWAN - Linda Indriani Agustin; M. Hufron; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted at PT.Catur Mulia Mandiri. The purpose of this research is to test and analyze the influence of leadership style, organizational commitment, Reward and Punishment towards employee work ethic of PT. Catur Mulia Mandiri. The variables used are leadership styles, organizational commitments, Reward and Punishment nout as independent variables, while the employee work ethic variable is the dependent variable.The samples used in this study were 67 PT employees. Chess Mulia Mandiri uses the method of random stratification proportional.Data collection method by collecting primary and secondary data. The analyses used include instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing and coefficient of determination test. Research shows that there is a positive and significant influence between leadership style, organizational commitment, reward and punishment towards employee work ethic at PT. Catur Mulia Mandiri.The research show that the leadership style variable has no significant effect on the employee work ethic of PT. Catur Mulia Mandiri.The variable of organizational commitment has a significant effect on the employee work ethic of PT.Catur Mulia Mandiri The Reward and Punishment variable has significant effect on the employee work ethic of PT. Catur Mulia Mandiri. Keywords: leadership style, organizational commitment, Reward and Punishment and employee work ethic